Role of computed tomography angiography for acute gastrointestinal bleeding - Chul-min Lee; Jong Keon Jang; Ji Hoon Shin; Soon-Young Song; Bo-kyeong Kang (Gastrointestinal Intervention, 2018)
Acute gastrointestinal (GI) bleeding is a common cause of emergency department admission and hospitalization. Diagnosis and treatment requires promptly with a multidisciplinary approach to reduce morbidity and mortality of acute GI bleeding. Many diagnostic modalities are being used in the evaluation of GI bleeding, each with its own strengths and weaknesses. With the recent advances in technology, computed tomography (CT) angiography has become an effective first-line method for imaging the cause of GI bleeding to guide management. The purpose of this review is to discuss diagnostic modalities of GI bleeding, with a focus on the emerging role of CT angiography.